Physiological, biochemical, and transcriptomic analyses reveal potential candidate genes of Platostoma palustre in response to salt stress - Changqian Quan; Suhua Huang; Qiaoling Yu; Zhining Chen; Muhammad Haneef Kashif; Meihua Xu; Fan Wei; Danfeng Tang (BMC Plant Biology)
Abstract Background Salt stress poses a genuine threat to plants, impeding their growth, development, and yields. Platostoma palustre (Blume) A.J.Paton (P. palustre) is an important medicinal plant in tropical and subtropical regions; however, the molecular mechanisms underlying P. palustre response to salt stress remain poorly understood. To better understand the molecular response of P. palustre plants to salt stress, we employed an integrated approach based on physiological, biochemical, and transcriptomic analyses. Results In this study, salt stress significantly restrained the growth of P. palustre and led to the accumulation of antioxidant enzymes (SOD, POD, and CAT). Besides, the chlorophyll content significantly decreased with the increase in NaCl concentration. Transcriptomic analysis revealed 8,679 differentially expressed genes (DEGs) (4,334 were up-regulated and 4,363 were down-regulated) between control (CK) and salt stress (150 mM NaCl). KEGG enrichment analysis showed that these DEGs were significantly enriched in “plant hormone signal transduction”, “MAPK signaling pathway-plant”, “photosynthesis - antenna proteins”, “starch and sucrose metabolism”, etc. Among the DEGs, 409 DEGs were identified as transcription factors (TFs), belonging to 25 families including MYB_superfamily, AP2/ERF, C2C2, bHLH, NAC, WRKY, and so on. In KEGG enrichment analysis of the identified TFs, 13 showed significant enrichment in “plant hormone signal transduction”. Notably, EIN3 (TRINITY_DN3357_c1_g2) and ERF1 (TRINITY_DN8842_c0_g1) involved in the ethylene (ETH) signaling were suggested potential candidates for salt stress response in P. palustre. Conclusions This study unravels key salt-responsive genes in P. palustre, facilitating the development of salinity-resistance varieties.